دراسة وصفية تحليلية لاكتساب المفهوم المكاني - يعلاوي, خليدة (جامعة الوادي - University of Eloued, 2019)
الملخص: هدفت الدراسة الحالية الى التعرف على اكتساب المفهوم المكاني "بين"، لدى 192 طفل، ذكور وإناث، من عمر 3 الى 10 سنوات، لا يعانون من أية مشاكل صحية، مستواهم التعليمي جيد أو متوسط، اللغة الأم هي العامية، ومن مستويات ثقافية واقتصادية مختلفة. تم انتقائهم من بعض رياض الأطفال والمدارس الابتدائية بالجزائر العاصمة. ومن أجل تحقيق هذا الهدف، اتبعنا المنهج الوصفي التحليلي، بما أننا بصدد دراسة سير تطور المفهوم المكاني "بين" وذلك استنادا الى المقاربة النفسو لغوية. بعد تطبيق البنود التي تقيس المفهوم "بين"، من اختبار المفاهيم المكانية، على مجموعة الدراسة، بينت النتائج وجود فروق دالة بين الأطفال في فهم واستعمال المفهوم المكاني"بين " تعزى لمتغير السن، مما يشير الى أن تكوين هذا المفهوم يرتبط بالسن وبالنمو المعرفي للطفل.ABSTRACT:The present study aims to identify the acquisition of the spatial concept between” of 192 children, males and females, from 3 to 10 years old, who do not suffer from any health problems, their level of education is good or average, informal language is the mother tongue, and from different cultural and economic levels. They were selected from some gardens and elementary schools in Algiers. In order to achieve this goal, we followed the analytical descriptive approach, in order to study the evolution of the spatial concept "between", based the psycholinguistic approach After applying the measures of the concept "between", from the test of spatial concepts, on the study group, the results showed that there are significant differences, between children in understanding and using the spatial concept "Between", according to the age variable, indicating that the formation of this concept confuses the age and cognitive development of the child.
لدى الطفل الجزائري من عمر 3 الى 10 سنوات
مقال
Keywords: االمفهوم المكاني بين ; الطفل ; المقاربة النفسو لغوية; spatial concept between; child; psycholinguistic approach